Integrating Local Languages in Indonesian EFL Classrooms: A Literature Review on Pedagogical Implications - La Ode Rasmin; Samsudin Samsudin (PT. Global Research Collaboration, 2024)
Integrating local languages in English as a Foreign Language (EFL) teaching has become a significant area of inquiry within Indonesia's multicultural educational landscape. This literature review explores the role and impact of local languages in supporting English language acquisition among Indonesian students. By examining fundamental studies and theoretical perspectives, this review addresses the challenges and benefits of incorporating local languages in EFL classrooms, including the potential for enhancing students' cultural identity, cognitive development, and linguistic skills. Findings from various studies highlight the pedagogical value of translanguaging and other multilingual approaches that leverage Local languages as a bridge for understanding English. However, the review also underscores obstacles such as lack of teacher training, limited resources, and institutional constraints. This study emphasizes the need for a more inclusive EFL curriculum that respects linguistic diversity and promotes sustainable language practices in Indonesia. Recommendations for future research are provided, focusing on effective strategies for balancing local and global language competencies within EFL pedagogy.